Analysis of Science Literacy Skills of Banda Aceh SMP Students in Solving PISA Physics Problems - Hamid, Abdul; S, Soewarno; Tursina, Ulfa; Jannah, Khali (International Conference on Multidisciplinary Research, 2020)
The Program for International Student Assessment (PISA) is an institution that has examined thescientific literacy abilities of students aged 13-15 years old. From this program, it was found that thescientific literacy skill of Indonesian students is still below the international average. This study aimedto analyze the scientific literacy skills of students of SMP Kota Banda Aceh in solving PISA questionswith physics content. The subjects of this study were 90 grade VII and VIII grade students aged 13-15years. These students are randomly selected to represent high, medium and low abilities. The instrumentused in this study was the PISA standard scientific literacy questions with physics content. The resultsshowed that the level of scientific literacy skills of students of SMP Kota Banda Aceh in solving PISAquestions with physics content is categorized as medium. The results of the analysis also show that themain weakness is found in the aspect of using scientific knowledge in analyzing texts or articles.Keywords: Science literacy, PISA, physics contentÂ